Asian International Students’ Barriers to Reporting Sexual Harassment Incidents - Dey, Semonti (Journal of International Students, 2024)
Asian international students continue to suffer from sexually harassing behaviors on college campuses. However, there has been little to no reporting of the incidents that cause their distress. Drawing on narratives of Asian international students in a predominantly white institution, the current study examines the barriers that these students face while reporting a case formally to the institutional representatives. The findings suggest that the severity of the case, lack of departmental support, fear of retaliation and peer relationship are among the major factors that hinder them from making a formal report. Implications of this study lie in informing the institutional policies and departmental practices to design more inclusive environment for the international students.